Transnational connections; Diasporic (re)turns to Indonesia - van Beukering, Jorien (UI Scholars Hub, 2022)
In the twentieth century, decolonization sparked mass migration movements across the globe as former settlers left newly independent colonies for the former imperial metropole or a new country altogether. In the following decades, postcolonial migrants made new homes and created communities in their hostlands. Eventually, some travelled back to their country of origin, the former colony. Indisch Dutch returns to Indonesia are not uncommon and, although some members of the first generation visited Indonesia as tourists, accounts of (re)turns by the second and third generation are rare. To form a clearer picture of the transnational connections between Indonesia and the Netherlands, it is important to engage with Indisch Dutch travels to Indonesia after independence. By examining life narratives of second and third generation Indisch Dutch, this article investigates the complex relationships between diaspora, memory, nostalgia, and identity, and their impact on transnational relations between the two countries. Specifically, the paper examines accounts by Adriaan van Dis and Lara Nuberg about their journeys of return to Indonesia in the 2000s.